Materiality and Indigenous Agency: Limits to the Colonial Order (Argentinean Patagonia, Eighteenth–Nineteenth Centuries) - Buscaglia, Silvana (2017)
This paper highlights the agency of indigenous peoples in the manipulation, alteration, and/or definition of limits to the colonial order established in Patagonia by the end of the eighteenth century. Hence, it rests on the ideas of the ambivalence of power and intercultural relations. Interethnic relationships are explored in two case studies from the same colonizing project: “Nueva Colonia y Fuerte de Floridablanca” (San Julián Bay, Santa Cruz province) and “Fuerte San José” (Valdés peninsula, Chubut province). Social practices, material conditions of the colonial settlements, and particularly, the indigenous perceptions of the colonial posts are thoroughly considered. This information is thus intended to discuss the divergent trajectories of interethnic relationships, as well as to approach colonialism in Patagonia from the natives’ logics.